Single Center Study of Vaccination Breakthrough infection with SARS-CoV-2 Among Erbil Population in August 2021 - Al-Khayat, Zakarea Abdullah Yaseen; Faqi, Sharmeen Qadr; Hasan, Dlshad Abdullah; Falo, Dalia Yaqoub (Journal of Contemporary Medical Sciences, 2021)
Objectives: This is a first study to determine the incidence of COVID-19 infection in the post-vaccinated in Erbil city population. Methods: This prospective study was conducted in the Central Health Laboratory in Erbil City over a period from 1st to 31st of August 2021. All vaccinated & non vaccinated persons (18 years of age and above) who had symptoms suggestive of COVID-19 were engaged in the study . Nasopharyngeal swabs were collected and examined for SARS-CoV-2 by real-time RT-PCR implemented to all attendance according to World Health Organization guidelines. Results: A total of 2934 persons had attended the Central Laboratory for checking during the study period. From this total number,551 (18.8% ) were vaccinated while 2383 were nonvaccinated (81.2%). Sixty one persons (61, 11.1%) of the vaccinated group showed a positive PCR . The highest incidence of PCR positivity according to age range , gender and vaccine dose , were as follows: male (42; 68.9%), 33–47 years (36; 59%), second dose (36; 59%) respectively. Statistically, the differences of distribution of the PCR positivity concerning the these factors were : non-significant . The higher incidence of PCR positivity was among the nonvaccinated group ( 449,18.8% ) and statistically, the differences of distribution of the PCR positivity between both groups of vaccinated and the nonvaccinated was significant (p ≤ 0.05). Conclusions: Primarily the present study conclude that SARS-CoV-2 incidence among vaccinated persons was 11.1%. Overall the present data provides further assurances of the effectiveness of the vaccines even when the vaccine was not able to prevent completely the infection . Further studies are needed to explore this topic.